Forgive sins: rise of thalidomide - Yugandar Inakanti; Shiva Kumar (Our Dermatology Online, 2014)
Thalidomide was originally used as a Wonder Drug to treat morning sickness and insomnia in pregnant women in late 1950s. It became apparent in early 1960s that thalidomide treatment resulted in severe birth defects in thousands of children. Then it was banned in most of countries. Later on discovered anti-inflammatory and anti-angiogenic properties of Thalidomide proved to be useful for treatment of leprosy and multiple myeloma. A series of immunomodulatory drugs created by chemical modification of thalidomide have been developed to overcome the original devastating side effects. It's being investigated extensively as a treatment for many other severe cutaneous disorders and advanced cancers. We briefly review pharmacological and the therapeutic profile of thalidomide.